2017
DOI: 10.1111/jcpt.12644
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis comparison in new users of antitumour necrosis factor‐α and with existing disease‐modifying antirheumatic drug therapy

Abstract: Anti-TNF-α therapy was independently associated with increased risk of TB in patients with mild disease, but it was not significantly correlated in patients with severe disease after adjusting for confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
3
7
0
1
Order By: Relevance
“…On the other hand, analysis of the RR in gender subgroups showed significantly elevated risk only in men. This was consistent with a recent cohort study that reported being male as an independent risk factor for TB …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, analysis of the RR in gender subgroups showed significantly elevated risk only in men. This was consistent with a recent cohort study that reported being male as an independent risk factor for TB …”
Section: Resultssupporting
confidence: 93%
“…Age is a key demographic parameter that predisposes individuals to TB risk, a burden that increases with age . Moreover, age of ≥60 years was reported to be an independent risk factor for TB associated with anti‐TNF‐α treatment . Consistently, the mean age of TB‐incident cases in key anti‐TNF‐α registries was reported to range from 53.1 to 70.2 which were higher than that (41.9) in our study and a previous multicentre study from Turkey (43.6) .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…77 Daha sonra 2005 yılında İsveç'te yayımlanan başka bir kayıt çalışmasında TNFalfa inhibitörü ile tedavi edilen RA hastalarında TB riskinin 4 kat arttığı bildirilmiştir. 65 Bunun ardından TNFalfa inhibitörü kullanımına dair TB risk artışı farklı ülkelerdeki birçok kayıt çalışmasıyla doğrulanmış, [78][79][80][81][82][83][84][85][86][87] çeşitli meta-analizlerle de desteklenmiştir. 66,88 Bu nedenle TNF-alfa inhibitörü alması planlanan hastalarda TB riskinin taranması ve riske ilişkin koruyucu önlemler alınmasına yönelik uzlaşı raporları veya kılavuzlar da yayımlanmıştır.…”
Section: Tnf-alfa Inhibitörleri Ve Tüberkülozunclassified